1999
DOI: 10.1037/0278-6133.18.5.537
|View full text |Cite
|
Sign up to set email alerts
|

Relations of diabetes intrusiveness and personal control to symptoms of depression among adults with diabetes.

Abstract: The generalizability of a model linking illness characteristics to psychosocial well-being was tested in a cross-sectional study of 237 adults with type 2 diabetes. It was hypothesized that diabetic complications increase illness intrusiveness, which in turn increases depressive symptomatology either directly or indirectly by reducing personal control over health outcomes. Illness intrusiveness was defined as the result of disruptions of valued activities and interests due to constraints imposed by the illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
2
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 27 publications
3
35
2
5
Order By: Relevance
“…However, perceived consequences of diabetes may be more important in determining an individual's emotional response to diabetes. In adults, the perceived threat of diabetes, a combination of perceived severity and perceived susceptibility to complications, was predictive of depression (26,27). In adolescents, perceived impact and perceived severity of diabetes were both associated with emotional well-being, with greater impact and severity predicting poorer well-being (7,19,21,22).…”
mentioning
confidence: 91%
“…However, perceived consequences of diabetes may be more important in determining an individual's emotional response to diabetes. In adults, the perceived threat of diabetes, a combination of perceived severity and perceived susceptibility to complications, was predictive of depression (26,27). In adolescents, perceived impact and perceived severity of diabetes were both associated with emotional well-being, with greater impact and severity predicting poorer well-being (7,19,21,22).…”
mentioning
confidence: 91%
“…Perceived lack of control and illness intrusiveness have also been found to be associated with the development of depression in diabetic patients (Talbot et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of RA (Devins, Edworthy, Guthrie, & Martin, 1992) the domains in which the illness is most intrusive (apart from diet and health) are work and finances, domains which are not highly intrusive in those with IBS. Studies across many different illnesses such as ESRD, RA, Cancer, Lupus (Devins et al, 2001), Diabetes (Talbot, Nouwen, Gingras, Belanger, & Audet, 1999) and MS (Shawaryn, Schiaffino, Larocca, & Johnston, 2002) have shown that features of the chronic illness affect depression through illness intrusiveness and that these are an underlying determinant of the psychosocial impact of an illness (Dancey et al, 2002;Devins et al, 2001). Variables which moderate the effect of illness intrusiveness on depression and/or quality of life have been identified in many illnesses, e.g., age and gender (Devins et al, 1996), perceived stigma (Dancey et al, 2002;Devins, 1994) and stressful life events (Devins et al, 2006).…”
Section: Introductionmentioning
confidence: 99%